Heart of darkness - Conrad, Joseph (Penguin Books Harmondsworth, Middlesex, England, 1994)
In Conrad's haunting tale, Marlow, a seaman and wanderer, recounts his physical and psychological journey in search of the enigmatic Kurtz. Travelling to the heart of the African continent, he discovers how Kurtz has gained his position of power and influence over the local people. Marlow's struggle to fathom his experience involves him in a radical questioning of not only his own nature and values but the nature and values of his society